CP El Niño and PDO Variability Affect Summer Precipitation over East China - Wan-Jiao Song; Qi-Guang Wang (Advances in Meteorology)
The summer precipitation produced by the East Asian summer monsoon (EASM) is significantly affecting agriculture and socioeconomics. Based on the Precipitation Reconstruction dataset in East China from 1950 to 2017, we investigate the spatiotemporal variations of summer precipitation, influencing environmental factors and their relation with the EASM and the Pacific Decadal Oscillation (PDO) in both central Pacific (CP) El Niño developing and decaying years. Results indicate the following: (1) The evolutions of CP El Niño events modulate the summer precipitation anomalies in East China. In the cool PDO phase, CP El Niño causes enhanced precipitation anomalies in the decaying years but less precipitation anomalies in the developing years, and vice versa for the warm PDO phase. (2) Atmospheric circulation anomalies drive the moisture transportation and combine the motion of western Pacific subtropical high resulting in the variation of precipitation patterns. Anomalous cyclone over the western North Pacific and the sustained Western Pacific Subtropical High (WPSH) are favorable for the increment of summer precipitation. (3) The different CP El Niño-EASM relationship is caused by the influences of PDO on the evolution of CP El Niño. CP El Niño develops slowly (decays rapidly) and is associated with rapidly developing (slowly decaying) anomalous warming in the north Indian Ocean during the developing (decaying) years.